Aba tös — the bear fetish in traditional beliefs and ritual practices of the Khakass (end of XIX — mid XX century) - Burnakov V.A.; Tsydenova D.T. (Вестник археологии, антропологии и этнографии, 2016)
The article deals with studying the phenomenon of bear fetish called Aba tös by the Khakass people. The cult of tös is a phenomenon that has arisen and existed in a traditional environment, where the shape of the relationship between visible (rational) and invisible (irrational) peace is characterized by the absence of hard insurmountable borders. Moreover, the religious-mythological consciousness of the people has an idea (as a common thread) of direct intersection of these worlds and their constant interaction with each other. Periodic violation of these relations, as believers considered, may turn into an imbalance of nature and human life. For the latter, this is turning into a variety of disasters and misfortunes. The ritual practice of the traditional society, in this case, was focused on the restoration of the balance and as a consequence, on the resolution of conflicts arising between the worlds as well as on the protection of vital interests of the people. A huge role in this process was assigned to ministers of religion, including the shamans, as well as directly — tös'es.